Effects of corona space charge polarity and liquid phase ion mobility on the shape and velocities of water jets in the spindle jet and precession modes of water electro-spray. (November 2016) - Pongrác, Branislav; Krčma, František; Dostál, Lukáš; Kim, Hyun-Ha; Homola, Tomáš; Machala, Zdenko
Abstract: The paper presents the experimental study of the effect of ions of different mobilities (H +, Cl −, Li + and OH − ) in electrosprayed water solutions under atmospheric pressure conditions in air and in SF6 background gas. Generally, at the atmospheric air conditions, the main difference between water electrospray (ES) in positive and in negative polarities is the shape and elongation direction of the water jets propagating from the charged nozzle. These phenomena can be associated with the movement of ions in water (i.e. the mobility of ions) or with the influence of the corona discharge and its ionic space charge. A comparison of HCl and LiOH water solutions with inversed mobility ratios of cations and anions showed that the mobility of ions inside the liquid is not an important parameter determining this difference between two ES polarities. The combined measurements in atmospheric air and SF6 gas clearly showed that the only important factor determining the different shapes and propagations of the water jets for both polarities is the corona discharge and its ionic space charge. Highlights: Nozzle polarity affects the behavior of water electrospray in atmospheric air. Nozzle polarity does not affect the behavior of water electrospray in SF6 . Ion mobilities do not cause the difference between positive and negative electrospray. Corona regimes cause the difference between positive and negative electrospray.